Cash Turnover And Receivables On Profitability - Tio Devilishanti; Irwan Moridu; Fitriani Fitriani; Mardiana Ruslan; Cut Dina Handayani (International Journal of Management Research and Economics, 2023)
A company called PT. Trinusa Avia Mandiri provides ground handling services as well as other commercial endeavors that assist airport-based aviation enterprises. At the PT. Trinusa Avia Mandiri Halim Perdana Kusuma Airport Branch in Jakarta, the purpose of this study is to determine how the company's cash turnover and receivables affect profitability. Quantitative research is being conducted here. The purpose of hypothesis testing is to determine the degree to which the independent variable influences the dependent variable by using multiple linear regression analysis through the f and t tests. According to the study's findings, there is a partial relationship between cash turnover and profitability and receivables turnover, with a significance level of less than 7%. Furthermore, at a significance level below 7%,